Human bocavirus infection in children with acute gastroenteritis in Japan and Thailand - Ngan Thi Kim Pham (2018)
A total of 329 fecal specimens, which had been known to be negative for rotavirus, adenovirus, norovirus, sapovirus, and astrovirus, and which were collected from infants and children with acute gastroenteritis in Japan and Thailand during 2005-2008 were screened for human bocavirus (HBoV). HBoV was detected by PCR with a primer pair that amplified the NP1 region of its genome and was genotyped by sequencing of the VP1/VP2 region. Of the 329 samples tested, 6 (1.8%) were positive for HBoV. Of these, five samples were collected from Japan and one sample was from Thailand, and the detection rates of HBoV in each country were 2% and 1.2%, respectively. For the detected HBoV, the capsid VP1/VP2 gene of all HBoV strains was successfully sequenced. Four Japanese HBoV strains studied were clustered into group 1, while the remaining Japanese strain and a unique Thai strain belonged to group 2. No severe acute gastroenteritis associated with HBoV was noted. This study provides better understanding on the epidemiology of HBoV infections in children with acute gastroenteritis in Japan and Thailand. © 2010 Wiley-Liss, Inc.